Global occurrence of deoxynivalenol in food commodities and exposure risk assessment in humans in the last decade: a survey. Issue 8 (31st March 2022) - Mishra, Sakshi; Srivastava, Sonal; Dewangan, Jayant; Divakar, Aman; Kumar Rath, Srikanta
Abstract: Preventing food from fungal infestation has become a cause of great concern as food safety is of particular importance to public health globally. Recently International Agency for Research on Cancer (IARC) and the World Health Organization (WHO) in its 2016 press release has urged to take action against widespread mycotoxin contamination in developing countries. Deoxynivalenol (DON) is a group B trichothecene mycotoxin, produced by common field pathogens such as Fusarium graminearum and Fusarium culmorum, and reported to be the predominant contaminant of food commodities. At present, no detailed/systematic review regarding the global occurrence of DON in various food and grain samples is available in the literature. Considering DON's cosmopolitan behavior and toxicological manifestations, the present review summarizes the region-wise reports and surveys conducted across the globe during the last decade, on the occurrence of DON in the food commodities intended for human consumption. Studies conducted on DON metabolites either in food, urine or blood samples from humans have also been reviewed. The present review indicates that the current exposure levels of DON might pose a health risk for the consumers, especially in growing children, necessitating to take vigilant steps to guarantee food safety.